PENGARUH KEGIATAN EKSTRAKURIKULER BUDAYA TERHADAP PERILAKU SOSIAL SISWA KELAS X SMAN 10 PANGKEP - Imrayani; Hj.Fatimah Azis (STKIP Subang, 2024)
This study aims to analyze the impact of cultural extracurricular activities on the social behavior of tenth-grade students at SMAN 10 Pangkep. The method employed is qualitative research with a phenomenological approach, focusing on understanding the subjective experiences of students participating in these activities. A total of 15 students actively involved in various cultural activities, such as dance, music, and theater, were included in this research. Data collection was carried out through in-depth interviews and participatory observation. Semi-structured interviews were used to explore students' perspectives on how extracurricular activities influence their social interactions. Observations were made to document group dynamics and relationships among students during the activities. From a sociological perspective, this research explores the role of extracurricular activities as a means of socialization, where students learn important norms, values, and social skills essential for their social lives. Data analysis was conducted using thematic analysis, where interview transcripts were examined to identify key themes from the students' experiences. The findings indicate that participation in cultural extracurricular activities significantly enhances social skills, a sense of togetherness, and empathy among students. These activities also strengthen social bonds and promote tolerance toward differences, which are crucial for building a harmonious society. This study is expected to provide guidance for schools to design more effective extracurricular programs and encourage student participation in character and social development.